A study of temperature control in different designs of emergency drug transport bags - John Dingley (Anaesthesia, 2019)
We examined whether low melting point phase-change waxes might be used in the design of emergency drugtransport bags to reduce the known temperature extremes their contents can be exposed to. Two custom-made hollow-walled drug containers were placed within a pair of drug transport bags to three day/nightcycles which included periods of direct radiant sunlight. The wall cavities of one container contained air, whereas those of theother contained a paraffin wax with a melting point of 44–46 °C and a high latent heat of fusion (i.e. until fully melted, itstemperature will not increase further). We collected 25,920 sets of temperature data at six locations within and around both containers. We foundthat 97.8% and 84.7% of ampoule temperatures within the wax and air cavity containers, respectively, werewithin a target range of 15–40 °C over the study duration (Levene statisticW = 4279.1; Levene’s test for equalityof variance, p < 0.001). The temperature of the ampoules in the wax cavity container only exceeded 40 °C for 1.7% of thetime. Even when they did so, their temperature was attenuated to 40.3 °C, despite an ambient air temperatureof > 40 °C for 6.4% of the time (peak 46.9 °C) and a bag surface temperature of > 40 °C for 17.2% of the time(peak 64.4 °C). In contrast, the ampoule temperature within the air cavity container was above 40 °C for 17.1% of thetime (peak 54.1 °C). We suggest that the latent heat of fusion of phase-change materials may be used to improve the design of drugtransport bags to mitigate any temperature changes in the drugs stored within.